Effect of nutrient intake on some biochemical parameters in the first six months after sleeve gastrectomy - Alphan, M.E.; BATAR, NAZLI (My University, 2019)
Aim: The aim of this study is to determine the possible nutrient and protein deficiency in the first six months after sleeve gastrectomy and to determine its effect on some biochemical parameters. Material and Methods: This study is an intervention study including 102 patients (75 female and 27 male) aged between 18-65 years, who had undergone sleeve gastrectomy operation at the General Surgery Clinic of Şişli Florence Nightingale Hospital between 13.07.2017 and 06.01.2018 and been followed up by a dietician for at least six months postoperatively. Anthropometric measurements, three-day food intake, and biochemical parameters were followed pre-operatively and during the first six months. Results: There was a 27.4% decrease in body weight of the patients in first six months after surgery. Both decrease in body weight, and decrease in body fat ratio and body mass index were found statistically significant (p<0.001). A statistically significant difference was found between preoperative and postoperative 6th month biochemical parameters; serum HbA1c, insulin, uric acid, total protein, total cholesterol, HDL-cholesterol, LDL-cholesterol, triglyceride, iron, iron binding capacity, ferritin, zinc, vitamin D, calcium, parathormone, folate and vitamin B12 levels of the patients (p<0.001). The difference between 6th month serum total protein levels of patients using and not using whey protein powder in the first month after sleeve gastrectomy was found statistically significant (p=0.002). Conclusion: It should be kept in mind that regulating patients’ lifestyle with post-operative multidisciplinary team and regular follow-up, and supporting with active life are necessary for obesity treatment to be sustainable.

Amaç: Bu çalışmanın amacı sleeve gastrektomi sonrası ilk altı ayda olası besin ögesi ve protein yetersizliğini belirlemek ve bazı biyokimyasal parametrelere etkisini saptamaktır. Gereç ve Yöntemler: Bu çalışma, 13.07.2017 ve 06.01.2018 tarihleri arasında, Şişli Florence Nightingale Hastanesi Genel Cerrahi kliniğinde sleeve gastrektomi ameliyatı olan ve ameliyat sonrası en az altı ay uzman diyetisyen takibini sürdüren, 18-65 yaş arasında 102 hasta (75 kadın ve 27 erkek) ile yapılmış bir müdahale çalışmasıdır. Hastaların ameliyat öncesi ve ilk altı ay boyunca antropometrik ölçümleri, üç günlük besin tüketimleri ve biyokimyasal parametreleri takip edilmiştir. Bulgular: Ameliyat sonrası ilk altı ayda hastaların vücut ağırlıklarında %27,4 oranında azalma görülmüştür. Hem vücut ağırlığındaki azalma hem de vücut yağ oranındaki ve beden kütle indeksindeki düşüş istatistiksel olarak anlamlı bulunmuştur (p<0,001). Hastaların ameliyat öncesi ve post-op 6.ayda biyokimyasal parametreleri; serum HbA1c, insülin, ürik asit, total protein, total kolesterol, HDL-kolesterol, LDL-kolesterol, trigliserit, demir, demir bağlama kapasitesi, ferritin, çinko, D vitamini, kalsiyum, parathormon, folat ve B12 vitamini arasında istatistiksel olarak anlamlı fark bulunmuştur (p<0,001). Sleeve gastrektomi sonrası ilk ay protein tozu desteği kullanan ve kullanmayan hastaların 6. aydaki serum total protein seviyeleri arasındaki farklılık istatistiksel olarak anlamlı bulunmuştur (p=0,002). Sonuç: Obezite tedavisinin sürdürülebilir olması için ameliyat sonrası multidisipliner ekip ve düzenli takip ile hastaların yaşam tarzının düzenlenmesi ve aktif yaşamla desteklenmesinin gerekli olduğu unutulmamalıdır.
Sleeve gastrektomi sonrası ilk altı ayda besin ögeleri alımının bazı biyokimyasal parametrelere etkisi
Keywords: Bariatric Surgery; Nutrition; Sleeve Gastrectomy; Bariatrik Cerrahi; Beslenme; Sleeve Gastrektom